Edukasi Kefarmasian sebagai Upaya Preventif Diabetes Mellitus dan Gout di Kelurahan Mangkupalas Samarinda Seberang - Anggreini, Putri; Rijai, Laode; Herman, Herman; Ibrahim, Arsyik; Rashif Rijai, Hifdzur; Rozi, Fahrul; Rezky Khairun Nisaa, Nur; Olivia Siregar, Vita; Badawi, Satriani (Civiliza Publishing, 2025)
Pharmaceutical education is one of the preventive efforts to enhance community understanding of Diabetes Mellitus (DM) and Gout, whose prevalence continues to rise in society. Mangkupalas Village, Samarinda Seberang, was selected as the location for community service based on the high risk of DM and Gout influenced by dietary patterns, lifestyle, and a lack of health education. The service method included delivering preventive material on DM and Gout by resource persons, followed by a discussion session. Questionnaires were distributed before and after the educational activities. The results showed an average pre-test score of 48.8 and an average post-test score of 60.0, indicating an increase in community knowledge after receiving pharmaceutical education. Additionally, residents showed enthusiasm for implementing healthy lifestyle changes. In conclusion, pharmaceutical education is effective in raising awareness and knowledge about DM and Gout among the community. This community service activity can serve as a continuous effort to reduce the risk of chronic diseases, particularly among the residents of Mangkupalas Village, Samarinda.